1996
DOI: 10.1016/0014-5793(96)00617-5
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for CYP27 as a major renal mitochondrial 25‐hydroxyvitamin D3 1α‐hydroxylase

Abstract: A mitochondrial cytochrome P450 fraction catalyzing hx-and 27-hydroxylation but not 24-hydroxylation of 25-hydroxyvitamin D3 was purified from pig kidney. The ratio between the la-and 27-hydroxylase activities was the same in all purification steps including a side fraction. Attempts to separate the l~z-and 27-hydroxylase activities were unsuccessful. A monoclonal antibody directed against purified pig liver CYP27 recognized a protein of the same apparent Mr and immunoprecipitated both the hx-and 27-hydroxylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…These abnormalities undoubtedly resulted from the diminished capacity of vitamin D-deficient animals to optimally absorb calcium and the subsequent stimulus for parathyroid gland enlargement, overproduction of parathyroid hormone and consequent effects on renal phosphate handling. In the 1␣(OH)ase mutant mice, circulating 1,25(OH) 2 D 3 levels were undetectable by RIA, emphasizing the nonredundant role played by the renal 1␣(OH)ase in producing the hormonally active metabolite of vitamin D. It has been suggested that other enzymes such as the vitamin D-25-hydroxylase (CYP27) can catalyze 1␣-hydroxylation of 25(OH)D (27), and this might occur in the kidney (28). However, this phenomenon clearly does not occur to any major extent in the homozygous mice although the ability of other enzyme systems to carry out local 1␣-hydroxylation of vitamin D metabolites can now be studied further in the 1␣(OH)ase knock-out model.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities undoubtedly resulted from the diminished capacity of vitamin D-deficient animals to optimally absorb calcium and the subsequent stimulus for parathyroid gland enlargement, overproduction of parathyroid hormone and consequent effects on renal phosphate handling. In the 1␣(OH)ase mutant mice, circulating 1,25(OH) 2 D 3 levels were undetectable by RIA, emphasizing the nonredundant role played by the renal 1␣(OH)ase in producing the hormonally active metabolite of vitamin D. It has been suggested that other enzymes such as the vitamin D-25-hydroxylase (CYP27) can catalyze 1␣-hydroxylation of 25(OH)D (27), and this might occur in the kidney (28). However, this phenomenon clearly does not occur to any major extent in the homozygous mice although the ability of other enzyme systems to carry out local 1␣-hydroxylation of vitamin D metabolites can now be studied further in the 1␣(OH)ase knock-out model.…”
Section: Discussionmentioning
confidence: 99%
“…(41,42) Additionally, other cytochrome P450 enzymes besides the 1␣(OH)ase may be able to catalyze the 1␣-hydroxylation of 25(OH)D in the fetus. Thus, an alternative pathway has been reported for the mitochondrial cytochrome P450 CYP27, which normally carries out the hepatic 25-hydroxylation of vitamin D. (43,44) With the cloning of the mouse 1␣(OH)ase gene these issues can be explored further by developing a 1␣(OH)ase gene knockout mouse model, either whole animal or tissue specific and then generating a double knockout of both the 1␣(OH)ase and the VDR genes. Further studies will now be required to determine the precise mechanisms of action of the vitamin D autocrine/paracrine system components in bone, kidney, and gut, and their interaction with other mediators of growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, bile acid synthesis has been thought to occur solely in the liver, as Cyp7a1 is a liver-specific enzyme, however, an alternative or "acidic pathway" was discovered which starts with the side chain 27-hydroxylation catalyzed by Cyp27a1 [3]. Interestingly, Cyp27a1 is expressed in an array of extrahepatic tissues such as kidney [4], immune cells [5], and the brain [6] and mutations in the Cyp27a1 gene has been shown to underlie the sterol storage disorder cerebrotendinous xanthomatosis, which leads to cholesterol accumulation in the brain and neurological dysfunction [6]. The development of neurological dysfunction by the mutation of a key enzyme in bile acid biosynthesis poses the question of whether bile acids (or their intermediaries) play a physiological role in the brain under homeostatic conditions.…”
mentioning
confidence: 99%